2014
DOI: 10.1371/journal.pone.0104503
|View full text |Cite
|
Sign up to set email alerts
|

Smad4 Regulates Ureteral Smooth Muscle Cell Differentiation during Mouse Embryogenesis

Abstract: Proper formation of ureteral smooth muscle cells (SMCs) during embryogenesis is essential for ureter peristalsis that propels urine from the kidney to the bladder in mammals. Currently the molecular factors that regulate differentiation of ureteral mesenchymal cells into SMCs are incompletely understood. A recent study has reported that Smad4 deficiency reduces the number of ureteral SMCs. However, its precise role in the ureteral smooth muscle development remains largely unknown. Here, we used Tbx18:Cre knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Some of these models do not develop smooth muscle throughout the whole ureter [9], while others lack smooth muscle only proximally [64]. These lead, in turn, to dilation of the whole ureter [9] or just the proximal ureter [64]. This dilation is thought to result from a lack of peristalsis in the absence of smooth muscle.…”
Section: (A) Urinary Systemmentioning
confidence: 99%
“…Some of these models do not develop smooth muscle throughout the whole ureter [9], while others lack smooth muscle only proximally [64]. These lead, in turn, to dilation of the whole ureter [9] or just the proximal ureter [64]. This dilation is thought to result from a lack of peristalsis in the absence of smooth muscle.…”
Section: (A) Urinary Systemmentioning
confidence: 99%
“…The defection in urothelial differentiation can cause UPJO in mice (13). Previous studies have found increased Shh and decreased Gli3 expression in children with UPJO (4).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the role of Smad4 in limb formation, we utilized new Tbx18 Cre/ϩ knock-in mice (24), with which to remove Smad4 in the proximal domain of forelimbs and hindlimbs in mouse embryos (Fig. S1, A and B).…”
Section: Deletion Of Smad4 Disrupts Skeletal Developmentmentioning
confidence: 99%